Holistic Islamic Religious Education For Primary School Children - Aris Aris (UIN Siber Syekh Nurjati Cirebon, 2026)
Holistic Islamic religious education for primary school children is an approach that emphasizes the development of students as a whole, covering intellectual, spiritual, emotional, social, moral, and practical skills aspects. This article aims to examine the theoretical foundation of holistic Islamic religious education and its application based on Ki Hajar Dewantara's thoughts on elementary school students. The study is carried out through a conceptual approach by utilizing relevant educational, psychology, and philosophical theories. Religious learning is considered to be verbalistic, memorization-oriented, and lacks integration of cognitive, affective, and psychomotor domains. Holistic education offers solutions through the development of creation, taste, and karsa in an integrated manner. The pedagogical foundation emphasizes active participation, a conducive learning environment, character education, and appreciation for children's uniqueness. The psychological foundation is rooted in the Gestalt theory which views learning as a holistic activity, while the philosophical foundation is influenced by the thought of perennialism and the unity of man with reality. The application of Dewantara's theory is carried out through example, dialogue, and the provision of learning encouragement that is in accordance with the development of students. The findings of the study show that holistic Islamic religious education is relevant to form noble morals, thinking skills, worship discipline, and social responsibility so that students are able to internalize religious teachings in daily life.